الرقابة على القرارات الإدارية ووسائلها في النظام القانوني الليبي : دراسة مقارنة مع القانون المصري - رويحة، عبد الحكيم أمحمد علي
The aim of this research is to study the different control instruments or means applied on the legitimacy of administrative decisions in the Libyan legal system, and the effectiveness of these means in curbing the despotism of the executive authority and its administrative system, by placing its administrative decisions under the supervision of the legitimation principle. This all to achieve the state of rights in which both the ruler and the governed people are subject to the law. This study adopted an analytical and comparative approach, the analytical approach was used to analyze the concept of the administrative decisions’ legitimacy and its basic principles, and to explain the reasons behind the termination of the administrative decisions, whether with or without the will of the administration, besides, the analytical method has enabled the study to analyze the legal texts and judicial provisions related to this subject of the research. Through a comparative method, the study has compared the Libyan legal system with the Egyptian legal system to identify the similarities and differences, to properly define the concept of the principle of legality in the administration field, the reasons for the end of administrative decisions, and also to scientifically benefit from the Egyptian and other judicial rulings, which are rich of studies that are beneficial to this research. The finding of this study concluded on that the basis of the legitimacy of the administrative decision lies in its submission to the rule of law, this kind of submission is not restricting the administration’s work but disabling any kind of autocracy while making decisions. The study concluded also that not everything that comes from the administration is an administrative decision, as there are certain conditions and pillars that should be fulfilled to acquire the capacity to make such a decision. And for an administration to not be deviated from the principle of legality, it must be subjected to different instruments or means of control, the legislative authority has a supervision and control power over the executive authority, in the meantime, the administration has its own control power such as withdrawal and administrative cancellation power. There are also other means of control that are outside the power of administration, these means of administrative and financial control are owned by the legislative authorities which monitor and control the actions of the administration, holding them accountable for any offences in the decisions made. At the end, the Libyan judicial authority has its own instruments to control the legality of the administrative decisions under the title of annulment, limiting with that the administrative judge's authority to determine the legitimacy of the decision and to practice the annulment power if it is found illegal.